2013
DOI: 10.1117/12.2028079
|View full text |Cite
|
Sign up to set email alerts
|

Solar internal lighting system with an automated solar tracker for daylight harvesting

Abstract: The paper reports the design and realization of a solar internal lighting system equipped with a solar tracking system. Full visible spectrum solar light has been focussed using a solar concentrator and guided inside the building through optical fiber whose other end is coupled to a fiber texture for lighting in building during day hours. The developed system is found to be an efficient system for interior lighting during daytime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Biconvex lenses can help block UV radiation and have a better ability than single convex lenses in concentrating light (Andre & Schade, 2002) as described in Figure 4. The collector's size in this study takes a reference from Kumar et al (2013) research. He found that with a lens diameter of 50 cm and a focal length of 35 cm, the resulting temperature was 130 degrees Celsius, lower than other types and sizes of collectors as described in Sreelakshmi & Ramamurthy, (2022).…”
Section: Fiber Optic Daylightingmentioning
confidence: 99%
“…Biconvex lenses can help block UV radiation and have a better ability than single convex lenses in concentrating light (Andre & Schade, 2002) as described in Figure 4. The collector's size in this study takes a reference from Kumar et al (2013) research. He found that with a lens diameter of 50 cm and a focal length of 35 cm, the resulting temperature was 130 degrees Celsius, lower than other types and sizes of collectors as described in Sreelakshmi & Ramamurthy, (2022).…”
Section: Fiber Optic Daylightingmentioning
confidence: 99%